The use of infrared photography for the study of thermal fields of urban agglomerations and objects on their territory - Железняк, О.О. (Science-based technologies, 2017)
The article gives an overview of the infrared sensing usage for the study of urbanized landscapes’ temperature anomalies. Main parameters of orbital infrared sensing systems that allow the research of metropolitan areas heat zones are analyzed. Spatial resolution of space-based infrared sensing systems is discussed. It is also shown that space-based infrared sensing allows to highlight landscape structures with heightened temperature and detect temperature contrast between city territories and nearby suburban areas. Examples of Ukraine’s big cities infrared remote sensing are provided for Kyiv, Kharkiv, Odessa and Dnipro. It is shown that each city has its own temperature contrast features. Attention is drawn to anthropogenic origin of thermal emissions of urbanized landscapes’ structures.